2020
DOI: 10.1177/1556984519891966
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Right Minithoracotomy Versus Hemisternotomy for Mitral Valve Repair

Abstract: Objective Minimally invasive mitral valve repair has been increasingly adopted. Right minithoracotomy (RT) and lower hemisternotomy (HS) have each been associated with improved short-term outcomes; however, these approaches have not been directly compared to each other. The aim of this study was to compare long-term survival and durability of 2 minimally invasive approaches to mitral repair. Methods We ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…31 More recent studies have described no difference in mortality and stroke rate between the two groups thanks to experienced centers and better patient preoperative assessment regarding anatomy and clinical history. 13,24,29,31,32 In our study, postoperative atrial fibrillation (FA) and conduction block alteration with the need for a PM appeared more frequently in the EAC group. We have hypothesized that EABC means a no-touch technique with respect to the sinus node and left atrial roof, although, the literature lacks confirmation of this.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…31 More recent studies have described no difference in mortality and stroke rate between the two groups thanks to experienced centers and better patient preoperative assessment regarding anatomy and clinical history. 13,24,29,31,32 In our study, postoperative atrial fibrillation (FA) and conduction block alteration with the need for a PM appeared more frequently in the EAC group. We have hypothesized that EABC means a no-touch technique with respect to the sinus node and left atrial roof, although, the literature lacks confirmation of this.…”
Section: Discussionmentioning
confidence: 62%
“…In the first report, the EABC group registered more postoperative strokes than the EAC 31 . More recent studies have described no difference in mortality and stroke rate between the two groups thanks to experienced centers and better patient preoperative assessment regarding anatomy and clinical history 13,24,29,31,32 …”
Section: Discussionmentioning
confidence: 99%
“…The degree to which registry data are suitable to answer questions about surgical techniques, in particular the use of auxiliary technology, is limited. Despite many studies that included a large number of patients undergoing MIMVS, there is still debate regarding the superiority of a particular mini-access route and even conventional sternotomy [ 71 ]. A recent study which included the same mitral valve surgery data from the NHR concluded that based on an analysis of registry data there was no reason to assume superiority of MIMVS in general [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…1). [14][15][16][17][18][19][20][21][22][23][24] Only 1 study was randomized, and 2 studies were multicentric and prospective. The Supplemental Tables present the study characteristics, patient characteristics, baseline New York Heart Association functional status, underlying mitral valve pathology, surgical techniques applied during the procedure, and types of cannulations during sternal-sparing MVRp.…”
Section: Study Selection and Patient Characteristicsmentioning
confidence: 99%